Sala de aula invertida na formação de professores de química: um estudo de caso com o tema condutividade elétrica - (:unkn) unknown (Universidade Federal do Pampa, 2019)
In view of the importance of studies to identify active methods to guide teachers and students to a change that promotes the growth and autonomy of teaching and learning, it is necessary to research on such methods. This study aims to investigate the “Flipped Classroom” or “Flipped Classroom” method in the initial training of chemistry teachers. To this end, we evaluated the application of the hybrid pedagogical approach known as the Inverted Classroom with the theme of electrical conductivity. Then, a hybrid didactic sequence was carried out, experienced by a group of scholars from the Institutional Program for Teaching Initiation Scholarships (PIBID), from the Degree in Chemistry at the Federal University of Pampa, Bagé campus. Given this, it was found that students who are building their views as teachers, reflected and understood about the importance of active methodologies, for building knowledge throughout the process. It was found that the approach influences the teacher and the student to leave their comfort zone. The Inverted Classroom method leads to active learning, leading the teacher to be a mediator of knowledge and the student to be a protagonist in the construction of their knowledge.
Keywords: Metodologias ativas; Aprendizagem; Ensino; Active methodologies; Learning; Teaching; CNPQ::CIENCIAS EXATAS E DA TERRA